Study on Blast Pressure Resistance of Foamed Concrete Material - Ahmad Zaidi, A.M.; Abas, A.; Abdul Rahman, I.; Ghazali, M.I.; Ahmad Zaidi, N.H. (International Journal of Integrated Engineering, 2009)
Great demand exist for more efficient design to protect personals and critical components against explosion or blast wave, generated both accidentally and deliberately, in various blast scenarios in both civilian and military activities. Concrete is a common material used in protective design of structures. Recently, the demands on producing the lighter concrete material have become interest in concrete research. Foamed concrete is a possible alternative of lightweight concrete for producing intermediate strength capabilities with excellent thermal insulation, freeze-thaw resistance, high-impact resistance and good shock absorption. This paper explores the role and development of Blast Pressure Resistant Materials (BPRM’s) on foamed concrete. The explosive tests were conducted to determine the blast mitigating properties. The results show that when the foamed concrete density is increases the blast energy absorption capability will be decreases due to reduce of cavity volume. This is suggested that cavity plays an important role to dissipate and absorb the shock energy of the blast.